1985
DOI: 10.1002/ijch.198500118
|View full text |Cite
|
Sign up to set email alerts
|

The SN2 Transition State. 6: Breakdown of the Reactivity–Selectivity Principle in the SN2 Reaction of α‐Halocarbonyl Compounds. A Molecular Orbital Analysis [1]

Abstract: Abstract. A molecular orbital (MO) analysis of the SN2 transition state (TS) of o-carbonyl derivatives is described with various nucleophile leaving group pairs. On the basis of this analysis it is shown that the enhanced selectivity toward nucleophiles observed in e-halocarbonyl compounds is directly associated with SN2 rate enhancement. Both observations result from a stabilizing frontier orbital interaction between a high lying ,..-type three center orbital along the reaction coordinate axis and the carbon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Almost a century ago, it was shown that reactions, much later designated as S N 2, can have an enhanced rate in the presence of the substituent. , Later, it was shown that this was not a general phenomenon and weak nucleophiles do not have their rates of attack significantly enhanced. , This represents an apparent breakdown of the reactivity−selectivity principle . Amolecular-orbital analysis has shown that the increases in both selectivity and reactivity result from a stabilizing frontier orbital interaction between the carbonyl π system and a high-energy π-type three-center orbital situated along the reaction coordinate axis.…”
mentioning
confidence: 99%
“…Almost a century ago, it was shown that reactions, much later designated as S N 2, can have an enhanced rate in the presence of the substituent. , Later, it was shown that this was not a general phenomenon and weak nucleophiles do not have their rates of attack significantly enhanced. , This represents an apparent breakdown of the reactivity−selectivity principle . Amolecular-orbital analysis has shown that the increases in both selectivity and reactivity result from a stabilizing frontier orbital interaction between the carbonyl π system and a high-energy π-type three-center orbital situated along the reaction coordinate axis.…”
mentioning
confidence: 99%
“…The benzoyl group served to direct a C−H bromination with N ‐bromophthalimide ( 20 ) of α ‐aryl‐ α ‐fluoroacetophenone ( 21 ) to yield an α ‐bromo intermediate ( 22 ) that was reactive towards [ 18 F]fluoride. As a carbonyl functionality, the benzoyl group could also assist nucleophilic substitution at the α ‐carbon, in contrast to the detrimental effects of α ‐fluorine substitution [22] . Cleavage of the auxiliary from [ 18 F] 23 with aqueous KOH, gave the desired 18 F‐difluoromethylarene ([ 18 F] 24 ) in a one‐pot protocol (Scheme 6b).…”
Section: The 18f‐fluorination Approachmentioning
confidence: 99%
“…the α-carbon, in contrast to the detrimental effects of αfluorine substitution. [22] Cleavage of the auxiliary from [ 18 F]23 with aqueous KOH, gave the desired 18 Gouverneur and co-workers disclosed an approach to 18 F-difluoromethoxy derivatives exploiting the halex reactivity of α-bromo-carbonyl compounds in 2017 (Scheme 7a). [23] Ethyl α-bromo-α-fluoro(aryloxy)acetates were prepared from the relevant phenol in two steps, and these materials were radiofluorinated with [ 18 A third halex strategy was disclosed by Liang and coworkers in 2017 (Scheme 8a).…”
Section: Minireviewsmentioning
confidence: 99%
“…As a carbonyl functionality, the benzoyl group could also assist nucleophilic substitution at the α-carbon, in contrast to the detrimental effects of αfluorine substitution. [22] Cleavage of the auxiliary from [ 18 F]23 with aqueous KOH, gave the desired 18 Gouverneur and co-workers disclosed an approach to 18 F-difluoromethoxy derivatives exploiting the halex reactivity of α-bromo-carbonyl compounds in 2017 (Scheme 7a). [23] Ethyl α-bromo-α-fluoro(aryloxy)acetates were prepared from the relevant phenol in two steps, and these materials were radiofluorinated with [ 18 A third halex strategy was disclosed by Liang and coworkers in 2017 (Scheme 8a).…”
Section: 'Halex' (Halogen Exchange) 18 F-fluorinationmentioning
confidence: 99%